Analisis Pengetahuan dan Keterampilan Tenaga Kesehatan tentang Perawatan Bayi dengan Metode Kangarro Mother Care (KMC) - Olimpia De Araujo; Ns. Domingos Soares, S.Kep, MM, M.Enf (Elisabeth Health Jurnal, 2021)
Background: Low birth weight (LBW) because they do not have a complete temperature to deal with environmental changes in the high temperature intra uterine and extra uterine environment, because cold temperatures can affect. The KMC method can reduce the risk of hypothermia because the heat from the mother's body provides heat to the baby's body by direct skin-to-skin contact and greatly facilitates the mother in giving breast milk (ASI) to the baby, strengthens the affectionate relationship between mother and baby and reduces time stay in hospital. Research (Uwaezuoke, 2017) on the effectiveness of the kangaroo method on LBW, shows that the kangaroo method can strengthen the relationship between mother and baby as well as a positive effect on infant weight. Babies born with LBW are caused by the process of losing body heat through: evaporation, radiation, conduction and convection, because of subcutaneous fat, brown fat, and less glycogen stray sites (Merenstein & Gardner, 2002).Methods: This research has used quantitative research with a descriptive approach. Focus on nurses in the Perinatology nursing room, HNGV, Dili, Timor-Leste in March 2019.Results: Using the criteria for the KMC method on newborns treated in the HNGV neonatology inpatient ward, analysis of 38 indicators for health workers who provide services to infants. The results of the study show that answering all the criteria is not correct with a minimum number of 3% and a maximum of 91%. On another aspect they need to answer that all the criteria are correct with the results showing a minimum of 6% and a maximum of 100%.Conclusion: Hospitals (neonatology units) need to regularly hold special training related to KMC for health workers to improve and expand their knowledge.